Extreme Temperature Variability in the Southeastern United States: Trends in Mississippi State - Benjamin DAMOAH; Xolani KHALO (PT Keberlanjutan Strategis Indonesia, 2024)
Over the past century, Mississippi has experienced significant increases in average temperatures, contributing to a variety of environmental and socioeconomic challenges. Changing precipitation patterns, including more frequent and severe droughts, threaten the state’s agriculture and water resources. At the same time, increasingly intense storms and floods pose risks to infrastructure and human safety. This paper explores evolving climate patterns in Mississippi, focusing on increasing temperatures, changing precipitation patterns, and the increasing frequency of extreme weather events, and examines the broader implications of these extreme temperature trends for Mississippi’s economy, health, and livelihoods. Trend analysis shows that Mississippi experiences year-round precipitation, hot summers, and relatively mild winters. The warm waters of the Gulf of Mexico serve as a major source of moisture and help moderate temperatures along the Mississippi coast, which impacts tourism and agricultural productivity. Over the past thirty years, the average annual precipitation in Mississippi has been 58.9 inches, with the northern region receiving about 50 inches and the coastal region nearly 65 inches. The state’s average temperature is extremely high, with a record low of 53°F and a record high of 75.3°F. This paper offers valuable insights into how Mississippi can adapt to a warming climate while protecting its natural resources and communities. The analysis highlights the need for stronger climate adaptation strategies and policy interventions to mitigate these impacts, with a focus on sustainable land and water management practices. This paper provides valuable insights for policymakers, environmental scientists, and stakeholders seeking to address the state’s climate challenges.